2014
DOI: 10.1016/j.elecom.2013.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Observation of water transport in the micro-porous layer of a polymer electrolyte fuel cell with a freezing method and cryo-scanning electron microscope

Abstract: Micro-porous layers (MPLs) play an important role in the water management of polymer electrolyte fuel cells (PEFCs), however, the detailed mechanism of how the produced water is drained from these layers is not well understood. This paper observed the cross-sectional distribution of liquid water inside the cathode MPL to elucidate details of the phase state of the water transported through the MPL. The freezing method and cryo-scanning electron microscope (cryo-SEM) are used for the observations; the freezing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 13 publications
2
39
0
Order By: Relevance
“…This is consistent with the observation of Aoyama et al [24], where the liquid water accumulated in the CL but was unable to move into the MPL. Therefore, there must be other pathways for the liquid water to exit.…”
Section: Pore-size Distribution and Water Invasionsupporting
confidence: 82%
See 3 more Smart Citations
“…This is consistent with the observation of Aoyama et al [24], where the liquid water accumulated in the CL but was unable to move into the MPL. Therefore, there must be other pathways for the liquid water to exit.…”
Section: Pore-size Distribution and Water Invasionsupporting
confidence: 82%
“…Since the MPL was assumed to be more hydrophobic than the CL, these models predicted that with an increase in MPL thickness, the water would gradually flood the part of MPL adjacent the CL. Recent experiments, however, have casted doubts over this hypothesis [24]. For example, the observation of Aoyama et al [24] showed that their MPL remained dry even after liquid water had accumulated at the CL-MPL interface, indicating that the water did not move into the MPL and must have found alternative exits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The freezing method immobilizes the liquid water in the cell as ice forms by decreasing the temperature in a short time, and the cryo-SEM visualizes the ice distribution in the MPL at high resolutions at −150 °C [15]. The research has however not resolved a number of issues, including the effects of the MPL on in-plane distribution of liquid water at the CL surface and the overall cell performance, a better understanding of which would enable further advances in the water management.…”
Section: Introductionmentioning
confidence: 99%